Upper airway stimulation versus untreated comparators in positive airway pressure treatment-refractory obstructive sleep apnea - Mehra, Reena; Steffen, Armin; Heiser, Clemens; Hofauer, Benedikt; Withrow, Kirk; Doghramji, Karl; Boon, Maurits; Huntley, Colin; Soose, Ryan J.; Stevens, Suzanne; Larsen, Chris; Maurer, Joachim T.; et al. (Annals of the American Thoracic Society, 2020)
Rationale: Understand the impact of insurance coverage on sleep apnea outcomes for patients awaiting upper airway stimulation. - - Objectives: Examine the natural history of impact of upper airway stimulation treatment versus insurance denial (comparators) on sleep apnea outcomes. - - Methods: A parallel-arm experimental study design was used to compare objective sleep apnea measures and patient-reported outcomes in those who received upper airway stimulation approval versus denial in a multinational prospective study (NCT02907398). Wilcoxon rank-sum test and logistic regression models were used to assess for differences of objective and subjective outcome changes in those who underwent upper airway stimulation versus no treatment comparators. - - Results: A greater reduction in apnea-hypopnea index was observed in those who underwent upper airway stimulation (n = 230, follow-up: 360 ± 171 d) versus no treatment (n = 100, follow-up: 272 ± 278 d), that is, −19.1 ± 15.8 versus −8.1 ± 20.9, respectively, P < 0.001, with consistent findings observed with nocturnal hypoxia measures. Concordantly, a greater improvement noted with subjective measures of dozing propensity was observed in patients undergoing upper airway stimulation versus comparators (Epworth Score, −5.1 ± 5.5 vs. 1.8 ± 3.7, respectively, P < 0.001) and overall sleep-related patient-reported outcomes. Women and those with previous oral appliance use had a lower odds of insurance approval (odds ratio [OR], 0.40; 95% confidence interval [95% CI], 0.22-0.71 and OR, 0.35; 95% CI, 0.18-0.69, respectively). - - Conclusions: Objective and subjective sleep apnea burden was more improved in those receiving upper airway stimulation versus not. Results underscore the need to optimize clinical care pathways focused on effective treatment of patients with obstructive sleep apnea who are not upper airway stimulation-insurance eligible and prioritize public health policy initiatives to address insurance-based sex-specific disparities.